Management of the Female With Non-classical Congenital Adrenal Hyperplasia (NCCAH): A Patient-Oriented Approach - Livadas, Sarantis; Bothou, Christina (Frontiers in Endocrinology, 2019)
Νon-classical congenital adrenal hyperplasia (NCCAH) is considered to be a common monogenic inherited disease, with an incidence range from 1:500 to 1:100 births worldwide. However, despite the high incidence, there is a low genotype-phenotype correlation, which explains why NCCAH diagnosis is usually delayed or even never carried out, since many patients remain asymptomatic or are misdiagnosed as suffering from other hyperandrogenic disorders. For affected adolescent and adult women, it is crucial to investigate any suspicion of NCCAH and determine a firm and accurate diagnosis. The Synacthen test is a prerequisite in the event of clinical suspicion, and molecular testing will establish the diagnosis. In most cases occurring under 8 years of age, the first symptom is premature pubarche. In some cases, due to advanced bone age and/or severe signs of hyperandrogenism, initiation of hydrocortisone treatment prepubertally may be considered. Our unifying theory of the hyperandrogenic signs system and its regulation by internal (hormones, enzymes, tissue sensitivity) and external (stress, insulin resistance, epigenetic, endocrine disruptors) factors is presented in an attempt to elucidate both the prominent genotype-phenotype heterogeneity of this disease and the resultant wide variation of clinical findings. Treatment should be initiated not only to address the main cause of the patient’s visit but additionally to decrease abnormally elevated hormone concentrations. Goals of treatment include restoration of regular menstrual cyclicity, slowing the progression of hirsutism and acne, and improvement of fertility. Hydrοcortisone supplementation, though not dexamethasone administration, could, as a general rule, be helpful, however, at minimum doses, and also for a short period of time and, most likely, not lifelong. On the other hand, in cases where severe hirsutism and/or acne are present, prescription of oral contraceptives and/or antiandrogens may be advisable. Furthermore, women with NCCAH commonly experience subfertility, therefore, there will be analysis of the appropriate approach for these patients, including during pregnancy, based mainly on genotype. Besides, we should keep in mind that since the same patient will have changing requirements through the years, the caring physician should undertake a tailor-made approach in order to cover her specific needs at different stages of life.